Building maintenance management in Malaysian institutions of higher education, the context-specific application for information delivery system - Fathi, Mohamad Syazli (INSPEN, 2016)
Building maintenance practices were made more complex as they have evolved to be more sophisticated in design and functionality. However, these have brought numerous challenges to building?s owner including institutions of higher education. Lack of timely maintenance in any parts of the building as well as unreported failures could lead to a disastrous outcome. Nowadays, various system have been applied to overcome the building maintenance management challenges, such as computerized maintenance management system (CMMS). There are also a need to consider that accurate data can be accessed by the right person at the right venue and time. In managing building maintenance, the use of Smartphone or mobile technologies are gaining popular. However, without considering the user's needs the current application can only transfer static modes of information. Context-aware could made easy and responsive to fulfill the user needs if they being applied into building maintenance application. This research has proved the concept of an intelligent building maintenance application is achievable based on a study conducted in Malaysian public universities. The proof of concept prototype was developed and evaluated with practitioners based on the user requirements study conducted. The concept of supplying specific information and services to the building maintenance manager has become technically and financially feasible because of the capability of integrating the mobile devices, context-awareness features, and positioning technologies in the working prototype application. The prototype application proved that the concept was acceptable amongs the stakeholders and could contribute to the efficiency of computerized building maintenance management system in public universities.